2017
DOI: 10.1002/hep.29374
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐206 prevents the pathogenesis of hepatocellular carcinoma by modulating expression of met proto‐oncogene and cyclin‐dependent kinase 6 in mice

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal cancers worldwide and therapeutic agents for this malignancy are lacking. MicroRNAs play critical roles in carcinogenesis and present tremendous therapeutic potential. Here we report that microRNA-206 is a robust tumor suppressor that plays important roles in the development of HCC by regulating cell cycle progression and cMet signaling pathway. MicroRNA-206 was under-expressed in livers of two HCC mouse models, human individuals bearing HCC, and human H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 46 publications
5
64
0
Order By: Relevance
“…Emerging evidence has demonstrated that dysregulation of miRNAs has a crucial role in the carcinogenesis and progression of HCC (25)(26)(27). A previous study (28) showed that miR-205 expression levels decrease in HCC tissues as compared with those in matched healthy tissues, and down-regulation of miR-205 promotes stemness of HCC by targeting PLCb1 and increasing CD24 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that dysregulation of miRNAs has a crucial role in the carcinogenesis and progression of HCC (25)(26)(27). A previous study (28) showed that miR-205 expression levels decrease in HCC tissues as compared with those in matched healthy tissues, and down-regulation of miR-205 promotes stemness of HCC by targeting PLCb1 and increasing CD24 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In line, we demonstrated p27 as a miR-494 direct target gene in HCC cell lines and xenograft mice playing a role in cell cycle fastening and cell proliferation in miR-494 overexpressing Huh-7 cells, suggesting that both animal models might be suitable for identification of miR-494 downstream molecular mechanisms [15]. Similarly, miR-206 was commonly downregulated among c-Myc and AKT/Ras-oncogene induced HCC mouse models, HCC cell lines, and human HCCs contributing to tumor development and progression through cell cycle regulator cyclin D1 (CCND1), c-MET, and cyclin-dependent kinase 6 (CDK6) direct targeting, as demonstrated by in vitro and in vivo experiments [21]. Notably, oncogene overexpression might be obtained not only through the establishment of TG mice but, more easily, through hydrodynamic tail-vein injection, which is an efficient procedure to deliver nucleic acids, primarily to the liver, taking advantage of its peculiar fenestrated sinusoids.…”
Section: Oncogene-related Tg Micementioning
confidence: 93%
“…The second strategy considered miRNA mimics modified at 2'O-methyl and labeled with four cholesterol groups, to increase the stability and transfection efficiency. Both strategies showed a marked anticancer effect in c-Myc mice, decreasing tumor growth and target genes expression, but failed to repress tumor growth of AKT/Ras mice, perhaps due to their more rapid growth, underlining the importance to test miRNA-based therapeutics in different animal models and suggesting again the need for patient stratification based on genomic and transcriptomic backgrounds [21]. In the following paragraphs, we describe miRNA-based antitumor approaches in xenograft and orthotopic HCC mouse models, focusing on their representativeness of human pathology and translation into the clinics (Figure 1).…”
Section: Hcc Mouse Models and Mirna-based Therapeutic Approachesmentioning
confidence: 99%
“…Therefore, they have many predicted and validated common targets, such as ARPC3, c-Met, VEGFA. [26][27][28] Figure 3A Figure S3). However, the combination of miR-1-3p or miR-206 mimics and gefitinib, significantly inhibited HGF-induced pc-Met expression.…”
Section: Mir-1-3p/mir-206 Target C-met In Egfr Mutant Nsclc Cell Linesmentioning
confidence: 99%